1955
DOI: 10.1071/ar9550446
|View full text |Cite
|
Sign up to set email alerts
|

Observations on survival and growth to weaning of lambs from ewes with defective udders.

Abstract: Although work has been published showing relationships between milk production of the ewe and growth of the lamb, little has been done to investigate the effects of physical impairment or deficiency in mammary function in the ewe on the survival and growth of the lamb. This point has been studied by examining data for survival, birth weight, daily gain in weight to weaning age, and weaning weight from 621 Merino lambs born in the F. D. McMaster Field Station, C.S.I.R.O., flock from 1946 to 1949. When the perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
13
0
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 0 publications
5
13
0
1
Order By: Relevance
“…In the present study, offspring of ewes with clinical mastitis had lower growth rates. This is in agreement with previous studies in which lambs born to ewes with mastitis had reduced growth rates (Hayman et al 1955;Watson and Buswell 1984;Arsenault et al 2008). A variety of bacterial species have been identified as being involved in ovine mastitis in New Zealand commercial ewes (Quinlivan 1968(Quinlivan , 1972Clark 1980), with Staphylococcus aureus being of particular importance at lambing (Quinlivan 1972).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In the present study, offspring of ewes with clinical mastitis had lower growth rates. This is in agreement with previous studies in which lambs born to ewes with mastitis had reduced growth rates (Hayman et al 1955;Watson and Buswell 1984;Arsenault et al 2008). A variety of bacterial species have been identified as being involved in ovine mastitis in New Zealand commercial ewes (Quinlivan 1968(Quinlivan , 1972Clark 1980), with Staphylococcus aureus being of particular importance at lambing (Quinlivan 1972).…”
Section: Discussionsupporting
confidence: 90%
“…In this study, udder palpation score at all observation times was associated with lamb growth to weaning, with lower growth rates in lambs born to ewes with abnormal scores compared to those born to ewes with normal scores. There are limited comparable data available; Hayman et al (1955) reported lambs born to ewes with defective udders grew up to 34 g/day less than those born to ewes with normal udders, while Grant et al (2016) reported offspring of ewes with intramammary lumps grew 10 g/day less than those without lumps. Based on the results of the present study, and assuming a mean lamb age at weaning of 84.4 days, lambs born to ewes with abnormal udder palpation scores would on average be 1.0-2.9 kg lighter at weaning than those born to ewes with normal udder palpation scores.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations